2004
DOI: 10.1038/sj.leu.2403421
|View full text |Cite
|
Sign up to set email alerts
|

Induction of differentiation of human myeloid leukemia cells by jasmonates, plant hormones

Abstract: Some regulators of plant growth and differentiation have been shown to induce the differentiation of several human myeloid leukemia cells, and might be effective as differentiation inducers to control acute myelogenous leukemia cells. In this study, the growth-inhibiting and differentiation-inducing effects of jasmonates on human myeloid leukemia cells were examined. Several myeloid leukemia cells were cultured with methyl jasmonate (MJ) and its derivatives. Cell differentiation was determined by nitroblue tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 29 publications
2
61
0
Order By: Relevance
“…Of particular interest here is the potential of jasmonates or derivatives thereof in hematolymphoid malignancy. The earliest reports of jasmonate activities included suppressed proliferation and induced apoptosis of AML, lymphoblastic leukemia, and lymphoma cell lines (25,43,44). This activity was shown to be selective because normal peripheral blood lymphocytes were spared even in mixed populations with chronic lymphocytic leukemia cells (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest here is the potential of jasmonates or derivatives thereof in hematolymphoid malignancy. The earliest reports of jasmonate activities included suppressed proliferation and induced apoptosis of AML, lymphoblastic leukemia, and lymphoma cell lines (25,43,44). This activity was shown to be selective because normal peripheral blood lymphocytes were spared even in mixed populations with chronic lymphocytic leukemia cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…It therefore remains to be determined whether the MSO generation reported here is a direct effect of MeJ or is an epiphenomenon of mitochondrial damage. Furthermore, Ishii and colleagues (43) previously showed that MeJ-promoted HL-60 cell differentiation was associated with increased mitogen-activated protein kinase (MAPK) activity. Treatment of HL-60 cells with the MAPK inhibitor PD98059 both diminished this activation and the differentiation seen in response to MeJ.…”
Section: Discussionmentioning
confidence: 99%
“…Plant stress hormones of the jasmonate family, small hydrophobic molecules, have been previously shown to be endowed with anticancer capabilities (Fingrut and Flescher, 2002;Ishii et al, 2004), allowing for the prolonged survival of tumor-bearing animals (Fingrut and Flescher, 2002;Heyfets and Flescher, 2007) and suppression of the metastasis of murine melanoma . Indeed, jasmonates are selectively toxic toward cancer cells (Fingrut and Flescher, 2002;Rotem et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, it is reported the synthesis of numerous and varied series of derivatives of MeJA, predominantly halogenated (-Cl,-Br, -F) structures, which similar to JA and its derivatives, they exhibit interesting and in some cases potent anti-neoplastic properties (Ishii et al 2004;Reischer et al 2007;Park et al 2010;Zhao et al 2010), but it is noteworthy that in each of the proposed series does not have reported the production of derivatives with keto group reduced and the potential inhibition of cell growth observed with these series of compounds does not exceed the IC50 obtained with the derivatives reported here. Qian et al 2004 reported that synthetic hydroxyl-containing jasmonates may induce different levels of plant defense responses, which are associated with different levels of enhanced metabolic activity for secondary metabolite biosynthesis.…”
Section: Study On Tumor Cell Linesmentioning
confidence: 99%